Performance Of Storage Tanks Supported By Shallow & Deep Foundations - Akhila Manne; Prasad P. V S R (Deep Foundations Institute, 2022)
Storage tanks are heavily loaded thin-shelled structures that exert large loads on and require large foundations to support them. They are generally very sensitive to foundation settlements as it may hinder the performance of tanks resulting in significant commercial or social impacts. Selection of their foundation is dependent on availability of suitable ground and limitations imposed by design specifications. Design of the tank foundations is generally based on theoretical methods and validation by representative field tests. This paper reviews settlement criteria for storage tanks as per national and international standards, case studies of large to medium diameter tanks supported on deep foundation i.e., bored cast-in-situ piles and shallow foundations on improved ground and their performance during load tests & hydro-tests is discussed. Paper concludes that storage tanks can also be supported on shallow foundations resting on improved ground reducing the settlement, time and cost significantly depending on the sub-soil.